THE INFLUENCE OF MOTIVATION, WORK DISCIPLINE AND COMPENSATION ON EMPLOYEE PERFORMAMNCE OF AJB BUMIPUTERA 1912 - Herlina; Sasono, Heri Sasono (JURNAL EKONOMI AKUNTANSI MANAJEMEN AGRIBISNIS, 2024)
Performance within the company needs to be improved so that the company obtains profits and survives in the long term. The purpose of this research is to see what factors influence employee performance at AJB Bumiputera 1912. Research analysis uses the t test, anova and correlation tests, multiple linear regression using SPSS version 26 and a research sample of 160 out of a population of 256 employees. The conclusions of this research are as follows: (1) Motivation has a positive and significant effect on the performance of AJB Bumiputera 1912 employees. (2). Work discipline has a positive and significant effect on employee performance at AJB Bumiputera 1912. (3). Compensation has a positive and significant effect on employee performance at AJB Bumiputera 1912. Thus the third hypothesis is accepted and supported by empirical evidence. (4). The research results provide evidence that Motivation, Work Discipline and Compensation have a significant effect on the performance of employees at AJB Bumiputera 1912.